Strategic Human Resource Management Practices: Barriers and Implications - Abang Ekhsan, Abang Othman (Nicolae Titulescu University and University of Bucharest,Romania, 2009)
Despite over twenty years and the supposedly tremendous change on the role of human resource management (HRM) the issue on the barriers to effective implementation of strategic human resource management (SHRM) remains unresolved. Why is this happening in practice and what are the causes? This critical and yet unresolved questions poses a major challenges to CEO’s, HR practitioners and line managers and is critical for continuous research. Similarly, the review of the literature indicates a serious lack in this area of research. This study will empirically examines the barriers to effective implementation of SHRM practices and is enhanced by combining multiple methods such as questionnaire surveys, case studies and multiple interviews with management, HR practitioners and line managers. Overall 87 questionnaires were analyzed. In addition, 25 interviews were conducted. The findings have shown that the barriers are similar and consistent among the Malaysian owned companies and the two major Japanese owned multinational companies in Malaysia. However, the degree of barriers among the two Japanese owned companies is much lower. Some of the notable findings on the barriers among Malaysian owned companies are the widely held view that HRM function is confined to routine administration function, reactive, fire-fighting, too job focused and its rigid organizational structure. Additionally, there is evidence that HR has not been able to execute as strategic business partner role in view of HR lacks of credibility and capability. In contrast, the lower barriers to effective implementation of SHRM practices among the two Japanese companies are attributed to their Japanese management systems (JMS) which have a highly elaborated and HR practices that are well integrated with their organizational goals. The findings may not claim to be exhaustive and conclusive, in view of other contextual and external factors that might not have been addressed. Nevertheless, the empirical findings from HR managers and line management of different functional levels, with different perceptions on factors leading to barriers to effective implementation of SHRM practices enables cross validation of issues, providing some practical insights and highlights the barriers and issues impacting on SHRM practices.